VARIABILITY OF SPIKE PRODUCTIVITY IN F2 HYBRIDS OBTAINED BY CROSSING COMMON WHEAT VARIETIES NOVOSIBIRSKAYA 67, SARATOVSKAYA 29, AND PUZA-4 TO THE SKLE 123-09 MULTIFLORET LINE - V. S. Arbuzova; T. T. Efremova; P. Martinek; E. V. Chumanova; O. B. Dobrovolskaya (Вавиловский журнал генетики и селекции)
Parameters of spike productivity were evaluated in plants of populations F2 obtained by crossing the varieties Novosibirskaya 67, Saratovskaya 29, and Puza-4 with the Skle 123-09 line, characterized by the multifloret habit. Skle 123-09 differed significantly from the studied cultivars in spike density, but no significant differences were found in spike length or the number of spikelets per spike. Two-way analysis of variance in F2 hybrids showed that the «spike length» variability character was determined mainly by the genotypic environment and the interaction of the factors «genotype × environment». The variability of the character “number of spikelets” was determined mainly by environmental conditions. This was particularly true for cultivars Saratovskaya 29 and Puza-4, recommended for arid areas. The variability of the resulting «spike density» character was affected by environmental conditions, genotype, and the «genotype × environment» interaction. The examination of the F2 populations revealed plants with fan-shaped spikelets; high grain content, as in Skle 123-09; and the best performance of other spike traits. The selected plants will be used to fix the «multiple florets» character in the parental varieties.